Clathrin-mediated endocytosis is involved in uptake and toxicity of silica nanoparticles in Caenohabditis elegans. (25th September 2019) - Eom, Hyun-Jeong; Choi, Jinhee
Abstract: Silica nanoparticles (SiNPs) are one of the popular nanomaterials used in industrial manufacturing, synthesis, engineering, and medicine. Recently, mechanisms underlying toxicity of silica nanoparticles have been reported; however, their uptake mechanisms have still not fully understood. In this study, toxicity of SiNPs was investigated in the nematode Caenohabditis elegans by using microarray and pathway analysis focusing the uptake mechanisms and their impact on toxicity. Physicochemical characterization of SiNPs was performed using dynamic light scattering (DLS) and zeta potential. No mortality was observed after 24 h exposure to SiNPs. However, reproductive ability was significantly reduced at the same concentrations. To ascertain a global mechanism of toxicity, microarray was conducted on C. elegans exposed to 10 mg/L SiNPs (20% reduction in reproductive ability). Microarray results indicated that genes involved in reproduction, such as msp (Major Sperm Protein) genes, were significantly downregulated in C. elegans exposed to SiNPs. Pathway analyses on differentially expressed genes (DEGs) revealed that endocytic pathway as a major pathway involved in the uptake of SiNPs. Involvement of endocytic pathway in the uptake of SiNPs was assessed using specific inhibitors (methyl-β-cyclodextrin, chlorpromazine, and LY294002 for caveolin-, clathrin-, and pinocytosis-mediated endocytosis, respectively). The inhibitor assay indicated that an internalization process facilitated by clathrin-mediated endocytosis is involved in the uptake of SiNPs. Functional analysis using endocytosis defective mutants, (i, e. cav-1, cup-2, and chc-1 ) confirmed the role of endocytosis on the reproductive toxicity of SiNPs. Overall results suggest that clathrin-mediated endocytosis pathway is a potential mechanism of uptake of SiNPs in C. elegans that in turn, affects general toxic outcome, such as, decrease in reproductive ability. Highlights: Reproductive ability was significantly reduced by SiNPs exposure. The microarray profiling showed the uptake mechanism and reductive of fertility. The clathrin-mediated endocytosis pathway is involved in internalization of SiNPs.